Madaniy landshaft konsepsiyasining mohiyati (SCIENCE and SOCIETY, 2026)
The article describes the formation and development of scholarly concepts of the cultural landscape, its place within the system of modern landscapes, the essence and specific features of the cultural landscape concept, as well as the theoretical and practical significance of its study.